Combined Effects of Electric Stimulation and Microgrooves in Cardiac Tissue‐on‐a‐Chip for Drug Screening. Issue 10 (13th September 2020) - Ren, Li; Zhou, Xingwu; Nasiri, Rohollah; Fang, Jun; Jiang, Xing; Wang, Canran; Qu, Moyuan; Ling, Haonan; Chen, Yihang; Xue, Yumeng; Hartel, Martin C.; Tebon, Peyton; et al.
Abstract: Animal models and traditional cell cultures are essential tools for drug development. However, these platforms can show striking discrepancies in efficacy and side effects when compared to human trials. These differences can lengthen the drug development process and even lead to drug withdrawal from the market. The establishment of preclinical drug screening platforms that have higher relevancy to physiological conditions is desirable to facilitate drug development. Here, a heart‐on‐a‐chip platform, incorporating microgrooves and electrical pulse stimulations to recapitulate the well‐aligned structure and synchronous beating of cardiomyocytes (CMs) for drug screening, is reported. Each chip is made with facile lithographic and laser‐cutting processes that can be easily scaled up to high‐throughput format. The maturation and phenotypic changes of CMs cultured on the heart‐on‐a‐chip is validated and it can be treated with various drugs to evaluate cardiotoxicity and cardioprotective efficacy. The heart‐on‐a‐chip can provide a high‐throughput drug screening platform in preclinical drug development. Abstract : A heart‐on‐a‐chip platform enabled by microgroove structures and pulsatile electrical stimulation is developed for efficient screening of drugs inducing cardiotoxic or cardioprotective effects. The heart‐on‐a‐chip can rapidly form biomimetic cardiac tissues through well‐aligned and synchronously beating cardiomyocytes, which is expected to give more accurate evaluations on drug development and repurposing process.